PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN VIDEO - Bayu Amzari; Hendrizal; Dini Maielfi (LP2M Universitas Adzkia, 2025)
This study was motivated by the low learning outcomes in Pancasila Education among fourth-grade students at SD Islam Terpadu Buah Hati Padang. The students had not yet been able to develop their knowledge in problem-solving, and group learning was rarely implemented. This study aimed to describe the improvement of students’ learning outcomes through the implementation of the Problem Based Learning (PBL) model assisted by instructional videos. The method used was Classroom Action Research (CAR) with qualitative and quantitative approaches, conducted in two cycles. The research subjects were 27 fourth-grade students. The results showed improvement in several aspects: teaching module planning increased from 82% in Cycle I to 96% in Cycle II, the teacher aspect increased from 75.35% to 89.2%, and the student aspect increased from 73% to 92.8%. The average student learning outcome also increased from 78.1 in Cycle I to 92 in Cycle II. Therefore, the implementation of the PBL model assisted by instructional videos can improve the learning process and learning outcomes in Pancasila Education among fourth-grade elementary school students.